Biocompatible fluorescent polymers from PEGylation of an aggregation-induced emission dye. (April 2017) - Ma, Chunping; Xie, Gaoyi; Zhang, Xiqi; Yang, Liutao; Li, Yang; Liu, Hongliang; Wang, Ke; Wei, Yen
Abstract: Novel aggregation-induced emission (AIE) polymers (NS1 andNS2 ) were prepared through reversible addition fragmentation chain transfer polymerization of poly(ethylene glycol) monomethyl ether methacylate and a new AIE monomer with a vinyl group. TheNS1 andNS2 copolymers were characterized by gel permeation chromatography, 1 H NMR spectroscopy, FT-IR spectroscopy, X-ray photoelectron spectroscopy, which proved their successful syntheses. Such amphiphilic copolymers could self-assemble into fluorescent polymeric nanoparticles (FPNs) in water with good dispersibility, which were spherical in shape. The prepared FPNs ofNS1 had a size range of 50–150 nm, strong green fluorescence in aqueous solution with fluorescence quantum yield of 31%, and low critical micelle concentration (CMC) of 0.030 mg mL −1 . TheNS2 FPNs exhibited size range of 200–300 nm, intense green fluorescence with quantum yield of 38%, and CMC of 0.037 mg mL −1 . These FPNs were demonstrated highly biocompatible for cell imaging. By virtue of excellent biocompatibility via PEG modification, good particle stability with low CMC, and AIE fluorescent polymers with high photostability, the FPNs constructed in this work showed obvious advantages. This strategy should inspire new approaches to prepare novel biocompatible AIE fluorescent polymers for biomedical application. Highlights: Two novel aggregation-induced emission polymers were synthesized. The polymers could self-assemble into fluorescent polymeric nanoparticles (FPNs) in water. The FPNs showed excellent biocompatibility for cell imaging. The FPNs exhibited good particle stability and high photostability.